Effect of Using Alternative Protein Feedstuffs with Protease Supplementation in Diet on Growth Performance and Apparent Ileal Protein Digestibility of Broilers - Taelibhong, Manathaya; Attamangkune, Seksom; Ruangpanit, Yuwares (Journal of Mahanakorn Veterinary Medicine, 2019)
Two studies were conducted to evaluate the use of rapeseed meal and meat and bone meal as alternative protein feedstuffs with protease supplementation on growth performance, carcass traits and apparent ileal protein digestibility (AID) in broiler. Experiment 1, Broiler performance and carcass traits were evaluated using 1,200 male Ross 308 broilers. All birds were randomly divided into 4 dietary treatments with 10 replications (30 birds/replication). Experiment 2, AID was studied using 120 male Ross 308 broilers fed with 4 dietary treatments as in Experiment 1. Each treatment consisted with 6 replications (5 birds/replication). The dietary treatments were 1) corn-soybean basal diet [CS], 2) CS with reduced 0.5% CP+125 ppm. protease [CS(-)+P], 3) CS with rapeseed meal and meat and bone meal [CSRM] and 4) CSRM with reduced 0.5% CP+125 ppm. protease [CSRM(-)+P]. All diets were formulated to be isonitrogenous and isocaloric. Both experiments were assigned in CRD. During starter period (1-17 DOA), CSRM birds had lower BWG than that of the CS group (P<0.05). Whereas CS(-)+P and CSRM(-)+P groups had BWG, feed intake, FCR and mortality rate similar to that of the CS and CSRM groups, respectively. There was no significant difference of growth performance among dietary treatments during grower period (18-35 DOA) and throughout the experimental period (35 days). Percentage of breast yield was significantly lower in CSRM and CSRM(-)+P groups than that of the CS group (P<0.05). However, no significant difference of AID was observed among dietary treatments. Birds fed CSRM(-)+P diet had better ROI than the other groups. Therefore, rapeseed meal and meat and bone meal are able to be incorporated as alternative protein feedstuffs in broiler diet containing lower CP supplemented with protease to reduce production cost of broilers.